Developing Sustainable Livestock Production by Feed Adequacy Map: A Case Study in Pasuruan, Indonesia - R. Parmawati; Mashudi Mashudi; A. Budiarto; Suyadi Suyadi; A. S. Kurnianto (Tropical Animal Science Journal, 2018)
Feed is a main factor of sustainable livestock population, where the availability of suitable land for grass growth is urgent. Modern agriculture has dramatically reduced the diversity of forages due to the massive monoculture. This study was aimed to obtain data on the size of the existing land, distribution, potential feed production, and to obtain the carrying capacity based on feed adequacy map. The research was conducted on 6 dairy and beef cattle farms in Pasuruan Regency (7°38′S,112°54′E), East Java Province, Indonesia: Tutur, Puspo, Lumbang, Lekok, Grati, and Purwodadi. Population and distribution are represented spatially through thematic maps. The mapping using the Indonesia land-base map (Rupa Bumi Indonesia-RBI) scale 1: 25,000, GPS handsets, and surveyors. Nguling had the highest beef cattle population (15,519 AU), while Tutur had the highest dairy cattle population (22,033 AU). Farmers were able to provide feed in the form of food-crop waste. Bangil had the highest carrying capacity of feed and safe criteria followed by Pohjentrek, while Lekok, Tutur, Puspo, Lumbang, Purwosari, Nguling, and Prigen subdistricts had very critical criteria. Based on the overall feed index, Pasuruan had a vulnerable criteria. The land carrying capacity status between land availability (SL) and land requirement (DL) was deficit. Less than 15% of land had low water carrying capacity. By carrying capacity index of crops waste (CCICW), the carrying capacity of food crops was high. The land carrying capacity status was deficit.